2023
DOI: 10.21470/1678-9741-2021-0537
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronary Artery Disease on The Outcomes of Catheter Ablation in Patients with Atrial Fibrillation

Abstract: Introduction The objective of this study is to investigate the possible impact of coronary artery disease (CAD) on clinical outcomes of catheter ablation in patients with atrial fibrillation (AF). Methods Patients with AF who underwent coronary computed tomography and catheter ablation were enrolled. The presence of stenotic severity and plaque, characteristics of coronary arteries, clinical data, and adverse outcomes of catheter ablation were analysed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…There is evidence that coronary artery disease increases the risk of AF recurrence after electrical cardioversion, 3 though at least one study found no difference in recurrence after catheter ablation 10 . In the latter study, however, adverse clinical outcomes were more common in those with ischemic heart disease.…”
Section: Discussionmentioning
confidence: 95%
“…There is evidence that coronary artery disease increases the risk of AF recurrence after electrical cardioversion, 3 though at least one study found no difference in recurrence after catheter ablation 10 . In the latter study, however, adverse clinical outcomes were more common in those with ischemic heart disease.…”
Section: Discussionmentioning
confidence: 95%